Uma proposta de arquitetura de software limpa baseada em microsserviços - Dantas, Francisco C. (Universidade Federal Rural do Semi-Árido, 2021)
This article presents a study focused on the description and proposal of a clean software architecture based on microservices. We look for a more pragmatic specification of clean software architecture based on microservices, aiming at the open software lifecycle. The options regarding the chosen technologies will be used project standards in the development, deployment, operation and maintenance cycle that should minimize the cost and maximize the system’s service life giving more productivity to those involved.
Keywords: Arquitetura de software; Microsserviços; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO